Classical mechanics - Goldstein, Herbert; Poole, Charles P.; Safko, John (New Delhi: Pearson Education, 2000)
Classical Mechanics has been the standard in advanced classical mechanics courses for thirty years. It emphasizes formulations important for the study of modern physics which prepare students to apply the principles and mathematical techniques of classical mechanics in later study. By deepening and building student understanding of classical mechanics, the text helps students make the connections between classical and modern physics. For Sale in Indian subcontinent only Special Features: * The classic approach of this leading text has been revised and updated without increasing the overall length of the book. * Problem sets are now helpfully divided into "Derivations" and "Exercises."
Appendix A-B, 601-638p.; Bibliography 617-622p.; Index 625-638p.
Keywords: Mechanics; Physics